Cuproptosis-related gene FDX1 expression correlates with the prognosis and tumor immune microenvironment in clear cell renal cell carcinoma - Wang, Tao; Liu, Yufeng; Li, Qing; Luo, Yang; Liu, Dawei; Li, Bin (Frontiers in Immunology, 2022)
Background: Cuproptosis, a newly discovered form of cell death, is regulated by protein lipoylation and is related to mitochondrial metabolism. However, further research is needed to determine how the cuproptosis-related gene Ferredoxin 1 (FDX1) affects the tumor immune response and its prognostic significance in ccRCC. Methods: The Cancer Genome Atlas (TCGA) was utilized to screen for FDX1 expression in ccRCC and healthy tissues, and Gene Expression Omnibus (GEO) and the Human Protein Atlas (HPA) were used to validate the results. The relationship among FDX1 expression, clinicopathological parameters, and overall survival (OS) was assessed utilizing multivariable analysis and Kaplan–Meier survival curves. The protein network with FDX1 interaction was constructed with the online Search Tool for the Retrieval of Interacting Genes/Proteins (STRING). Gene Ontology (GO) and gene set enrichment analyses (GSEA) were performed, and a single-sample GSEA was conducted to investigate the relationship between FDX1 expression and immune cell infiltration in ccRCC. We investigated the association between FDX1 expression and the infiltration degree of immune cells and the corresponding gene marker sets using the Gene Expression Profiling Interactive Analysis (GEPIA) and TIMER databases. Results: When compared with normal tissues, ccRCC had significantly reduced levels of FDX1 expression (p < 0.05). Lower levels of FDX1 expression were strongly associated with higher grades of cancer and more advanced TNM stages. The findings of multivariate and univariate analyses illustrated that the OS in ccRCC patients with low FDX1 expression is shorter in contrast with that in the high FDX1 expression group (p < 0.05). Ferredoxin reductase (FDXR) and CYP11A1 are key proteins that interact with FDX1, and ccRCC that had a defect in the FDX1 enzyme was linked to a low number of invading immune cells and their corresponding marker sets. Conclusion: In ccRCC, decreased FDX1 expression was linked to disease progression, unfavorable prognosis, and dysregulated immune cell infiltration.